OATP1B3-1B7, a novel organic anion transporting polypeptide, is modulated by FXR ligands and transports bile acids - Malagnino, Vanessa; Hussner, Janine; Issa, Ali; Midzic, Angela; Meyer Zu Schwabedissen, Henriette E (American journal of physiology: Gastrointestinal and liver physiology, 2019)
Organic anion transporting polypeptide (OATP) 1B3-1B7 (LST-3TM12) is a member of the OATP1B [solute carrier organic anion transporter ( ) ] family. This transporter is not only functional but also expressed in the membrane of the smooth endoplasmic reticulum of hepatocytes and enterocytes. OATP1B3-1B7 is a splice variant of in which the initial part is encoded by , whereas the rest of the mRNA originates from the gene locus of . In this study, we not only showed that and the mRNA encoding for OATP1B3-1B7 share the 5' untranslated region but also that silencing of an initial exon lowered the amount of and of mRNA in Huh-7 cells. To validate the assumption that both transcripts are regulated by the same promoter we tested the influence of the bile acid sensor farnesoid X receptor (FXR) on their transcription. Treatment of Huh-7 and HepaRG cells with activators of this known regulator of OATP1B3 not only increased but also OATP1B3-1B7 mRNA transcription. Applying a heterologous expression system, we showed that several bile acids interact with OATP1B3-1B7 and that taurocholic acid and lithocholic acid are OATP1B3-1B7 substrates. As OATP1B3-1B7 is located in the smooth endoplasmic reticulum, it may grant access to metabolizing enzymes. In accordance are our findings showing that the OATP1B3-1B7 inhibitor bromsulphthalein significantly reduced uptake of bile acids into human liver microsomes. Taken together, we report that OATP1B3-1B7 transcription can be modulated with FXR agonists and antagonists and that OATP1B3-1B7 transports bile acids. Our study on the transcriptional regulation of the novel organic anion transporting polypeptide (OATP) 1B3-1B7 concludes that the promoter of solute carrier organic anion transporter ( ) governs transcription. Moreover, the transcription of OATP1B3-1B7 can be modulated by farnesoid X receptor (FXR) agonists and antagonists. FXR is a major regulator in bile acid homeostasis that links OATP1B3-1B7 to this physiological function. Findings in transport studies with OATP1B3-1B7 suggest that this transporter interacts with the herein tested bile acids.